Review of “A Study of Western Missionaries' Works on the Shanghai Dialect: Shanghai Speech from 1847 to 1950” - JIANG, Yilin (Journal of Research for Christianity in China (JRCC), 2025)
Review of “A Study of Western Missionaries' Works on the Shanghai Dialect: Shanghai Speech from 1847 to 1950”